Study protocol for a multisite randomised controlled trial of a rehabilitation intervention to reduce participation restrictions among female breast cancer survivors. Issue 2 (13th February 2020) - Stevens, Courtney J; Hegel, Mark T; Bakitas, Marie Anne; Bruce, Martha; Azuero, Andres; Pisu, Maria; Chamberlin, Mary; Keene, Kimberly; Rocque, Gabrielle; Ellis, Daphne; Gilbert, Tiffany; Morency, Jamme L; et al.
Abstract : Introduction: Many breast cancer survivors report an inability to fully participate in activities of daily living after completing cancer treatment. Reduced activity participation is linked to negative consequences for individuals (eg, depression, reduced quality of life) and society (reduced workforce participation). There is currently a lack of evidence-based interventions that directly foster cancer survivors' optimal participation in life roles and activities. Pilot study data suggest rehabilitation interventions based on behavioural activation (BA) and problem-solving treatment (PST) can facilitate post-treatment role resumption among breast cancer survivors. Methods and analysis: This protocol describes a multisite randomised controlled trial comparing a 4-month long, nine-session BA and PST-informed rehabilitation intervention (BA/PS) against a time-matched, attention control condition. The overall objective is to assess the efficacy of BA/PS for enhancing breast cancer survivors' activity participation and quality of life over time. A total of 300 breast cancer survivors reporting participation restrictions after completing curative treatment for stage 1–3 breast cancer within the past year will be recruited across two sites (Dartmouth-Hitchcock Medical Center and University of Alabama at Birmingham). Assessments are collected on enrolment (T1) and 8 (T2), 20 (T3) and 44 (T4) weeks later. Ethics and dissemination: Study procedures are approved by the Committee for the Protection of Human Subjects at Dartmouth College, acting as the single Institutional Review Board of record for both study sites (STUDY 00031380). Results of the study will be presented at national meetings and submitted for publication in peer-reviewed journals. Trial registration number: NCT03915548 ; Pre-results.